Effect of lifestyle and reproductive factors on the onset of breast cancer in female BRCA 1 and 2 mutation carriers. Issue 2 (10th December 2015) - Rieder, Viktoria; Salama, Mohamed; Glöckner, Lena; Muhr, Daniela; Berger, Andreas; Tea, Muy‐Kheng; Pfeiler, Georg; Rappaport‐Fuerhauser, Christine; Gschwantler‐Kaulich, Daphne; Weingartshofer, Sigrid; Singer, Christian F
Abstract : We here demonstrate that in BRCA1/2 mutation carriers, the birth cohort‐associated differences in the onset of breast cancer are profound and influenced by reproductive factors. Abstract: Background: The birth year‐dependent onset of breast cancer (BC) in BRCA1/2 mutation carriers suggests a risk‐modifying role for reproductive and life style factors. We therefore examined possible associations between these factors and age at diagnosis. Methods: Cox regression analysis and log‐Rank testing were used to estimate the effect of potential life style factors on the onset of BC in 197 BRCA mutation carriers. Results: Nulliparous BRCA mutation carriers developed BC earlier than those who had delivered (36.4 vs. 40.9; P  = 0.001). Similarly, smokers and women who had used oral contraceptives experienced an earlier cancer onset (39.0 vs. 41.4; P  = 0.05 and 39.3 vs. 44.9; P  = 0.0001, respectively). In multivariate analysis, oral contraceptive use (HR: 1.7; P  = 0.006) and birth cohort (< vs. ≥1965 HR: 4.5; P  = 0.001) were associated with an earlier BC onset, while previous pregnancies led to a delay (HR: 0.2; P  = 0.04). Mutation carriers born ≥1965 were less likely to have experienced pregnancies and more likely to have used oral contraceptives, and consequently developed BC at an earlier age (median age: 42 vs. 58; P  < 0.0001 log‐Rank test). Conclusion: We here demonstrate that in BRCA1/2 mutation carriers the birth cohort‐associated differences in the onset of BC are profound and influenced by reproductive factors.